Differentiation of Flavobacterium psychrophilum from Flavobacterium psychrophilum-like species by MALDI-TOF mass spectrometry. (December 2017) - Pérez-Sancho, Marta; Vela, Ana Isabel; Wiklund, Tom; Kostrzewa, Markus; Domínguez, Lucas; Fernández-Garayzábal, José Francisco
Abstract: Rainbow trout fry syndrome (RTFS) is an important infectious disease caused by Flavobacterium psychrophilum affecting farmed salmonids worldwide. Other Flavobacterium psychrophilum -like species ( F. plurextorum, F. oncorhynchi, F. tructae, F. collinsii and F. piscis ) have been isolated from diseased rainbow trout fry suspected of RTFS although the epidemiological and clinical relevance of these pathogens are unknown. The objective of this study was to evaluate the potential use of MALDI-TOF ( Matrix-Assisted Laser Desorption/Ionization-Time of Flight ) Mass Spectrometry as method for specific identification of F. psychrophilum and its differentiation from other F. psychrophilum -like species isolated from diseased fish. Fifty-three isolates were analyzed after the creation of the Main Spectrum Profile (MSP) of reference strains of each of abovementioned species. F. psychrophilum exhibited a mass spectra very different from those of F. psychrophilum -like species, with five peaks ( m / z 3654, 4585, 5388, 6730 and 7310) present only in F. psychrophilum isolates, and three peaks ( m / z 6170, 7098 and 9241) absent in F. psychrophilum but present in all F. psychrophilum -like species. All F. psychrophilum isolates were correctly identified and differentiated from the F. psychrophilum -like species by MALDI-TOF. Although this approach showed a limited ability to differentiate among F. psychrophilum -like species, its complementation with a few simple biochemical tests may represent an alternative approach for the routine identification of the Flavobacterium psychrophilum -like species. Highlights: MALDI-TOF MS is a reliable approach for accurate identification of F. psychrophilum . F. psychrophilum exhibited distinctive mass peaks useful as specific biomarkers MALDI-TOF differentiated F. psychrophilum from other F. psycrophilum -like species MALDI-TOF differentiated the species F. oncorhynchi, F. plurextorum and F . collinsii Species F. tructae and F. piscis were not clearly identified by MALDI-TOF.